Smart and Sustainable Planning for Cities and Regions Results of SSPCR 2022 - Bisello, Adriano; Vettorato, Daniele; Bottero, Marta; Kolokotsa, Dionysia (Green Energy and Technology, 2024)
This open access book includes a selection of innovative contributions presented at the 4th international conference "Smart and Sustainable Planning for Cities and Regions 2022", held in Bolzano, Italy in July 2022. Featuring 10 papers by academics and consultants, strongly rooted in practical experiences and international projects, it discusses current ground-breaking research in innovative and sustainable planning for cities, with a focus on the environmental, economic, and social challenges associated with the global sustainability transition and energy systems integration. The contributions are illustrative of the richness of the issues discussed and the breadth of the emerging themes, including innovative business models for building and infrastructure at district level, integrated sustainability assessment schemes for Positive Energy Districts, a material flow accounting model for regional metabolism, energy communities as a lever to promote historical and landscape values, optimized and electrified last-mile logistics, multi-criteria decision analysis tools to redefine center/periphery relationships, a framework for socio-spatial analysis related to social practices, design principles and communication technologies improving both indoor and outdoor public spaces, augmented nature-based solution coupling the green elements with the latest technologies to deliver healthier and more appealing cities.